RELATIONSHIP OF BODY SIZE TO BEHAVIOR IN KINTAMANI DOGS - Siswanto, Siswanto; Dharmawan, Nyoman Sadra; Puja, I Ketut; Putra, I Gusti Agung Arta (Buletin Veteriner Udayana, 2023)
The Balinese believe that body size (the ratio of body length to snout length) in dogs is related to behavior, therefore body size is used to predict dog character. How to predict by measuring body size is a local wisdom that is still trusted for choosing a good dog. This belief has been running for a long time from their ancestors and has become a culture. Dog behavior according to local wisdom in Bali in general and in Sukawana Village, Kintamani District, Bangli Regency in particular, is categorized as: guna, jaya, forced, tek and kyul. Guna is a dog with an obedient character, useful and suitable as a hunting dog. Jaya is a dog with good character, attractive, energetic, tends to be hyperactive, this type of dog is also good for hunting. Force is a dog that is difficult to manage, requiring special handling, suitable for keeping the house. Tek is a dog with dirty behavior and difficult to train or manage and Kyul is a dog with a lazy character. A total of 66 Kintamani dogs were used as experimental animals. The research design used a cross-sectional study design. Body size observation data was then compared with clinical observations in the same dog. The results show that there is a relationship between behavior and body size (ratio of body length to snout length). It was concluded that body size (body length to snout length ratio) can be implemented to predict behavior.